Bullying e depressão no contexto escolar: um estudo psicossociológico - Silva, Celeste Moura Lins (2010)
Nowadays there are two phenomena occupying a prominent position in the school context which is worrying health, education and related areas professionals, violence and depression. The violence at school, called bullying is regarded as one of the biggest problems plaguing the entire community of educators, families and all segments of the society. Depression, for its part has been identified as one of the syndromes which is more present in the school context. As consequences of the first we can point their depression, low self-esteem, stress, absenteeism or truancy, attitudes of self-flagellation and even suicide, all these signs are also present in depression. In this sense this study aims to examine the social representations (SR) of the students inserted at public and private schools in the city of João Pessoa about depression and bullying and check if there is any relationship between these two phenomena so prevalent in the school context. The participants were 300 adolescents, boys and girls, aged between 12 and 18. All answered a sociodemographic questionnaire, the Free Word Association Technique, the Children's Depression Inventory (CDI), the Scale of perceived Acoso school and the instrument Scriped-Cartoon Narrative Bullying. From the results arising from the demographic questionnaire outlined the profile of adolescents through the CDI and the EAP was possible to track young people who experienced depression and were experiencing bullying. The Free Association of Words Technique allowed the understanding of the social representations of depression and violence. The instrument Scriped Cartoon Narrative Bullying also allowed the seizure of SR about bullying through consensual and idiosyncratic elaborations of the research participants. Depression was objectified elements marked by low self-esteem, negativity, distress, anxiety, nervousness, despair, disaffection and anchored in the psycho-sphere. Bullying has been objectified by the elements of pranks by physical aggression (pushing, knocking, punching, pulling clothes, hair) and verbal (cursing, swearing call To call, deleting, banning from participating in the play), and rooted in physical and psychological violence. The data also revealed that both the violence and the consequences such as depression cause imbalance in the psychological, cognitive, emotional, physical and behavioral spheres.